2007
DOI: 10.4269/ajtmh.2007.77.249
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorodiphenyltrichloroethane (DDT) for Indoor Residual Spraying in Africa: How Can It Be Used for Malaria Control?

Abstract: In 2006, the World Health Organization issued a position statement promoting the use of indoor residual spraying (IRS) with dichlorodiphenyltrichloroethane (DDT) for malaria vector control in epidemic and endemic areas. Other international organizations concurred because of the great burden of malaria and the relative ineffectiveness of current treatment and control strategies. Although the Stockholm Convention of 2001 targeted DDT as 1 of 12 persistent organic pollutants for phase-out and eventual elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 82 publications
1
73
0
Order By: Relevance
“…DDT is therefore credited with wholesale suppression and even complete disappearance of vector species such as Anopheles sergenti and Anopheles funestus from sizeable areas of Egypt, South Africa, Madagascar and Mauritius (Pampana, 1963;Curtis and Lines, 2000). Unfortunately, few African countries participated in the GMEC and even so, the reductions obtained were not sustained after the eradication period because limited resources were devoted to malaria control (Rogan and Chen, 2005;Sadasivaiah et al, 2007).…”
Section: Benefit Of Ddt Usementioning
confidence: 99%
See 3 more Smart Citations
“…DDT is therefore credited with wholesale suppression and even complete disappearance of vector species such as Anopheles sergenti and Anopheles funestus from sizeable areas of Egypt, South Africa, Madagascar and Mauritius (Pampana, 1963;Curtis and Lines, 2000). Unfortunately, few African countries participated in the GMEC and even so, the reductions obtained were not sustained after the eradication period because limited resources were devoted to malaria control (Rogan and Chen, 2005;Sadasivaiah et al, 2007).…”
Section: Benefit Of Ddt Usementioning
confidence: 99%
“…In India, IRS with DDT has been the mainstay of vector control for more than 5 decades. In general, reports to the WHO showed that the use of DDT for malaria vector control increased substantially among the African nations during 2000-2005 (Table 5), but decreased almost to zero in the Americas due to the signing of the North American Agreement on Environmental Cooperation, a side accord to the North American Free Trade Agreement (Sadasivaiah et al, 2007).…”
Section: Re-introduction Of Ddt Usementioning
confidence: 99%
See 2 more Smart Citations
“…Presently DDT is used for this method as it lasts longer than other insecticides currently approved by WHO [7]. DDT is however too stable and therefore is classed as a persistent organic pollutant that bio-accumulates in the ecosystem [8].…”
Section: Introductionmentioning
confidence: 99%